The histopathology of non-steroidal anti-inflammatory drug induced gastroduodenal damage: correlation with Helicobacter pylori, ulcers, and haemorrhagic events. Issue 7 (1st July 2001) - Frezza, M; Gorji, N; Melato, M
Abstract : Aims —The spectrum of microscopic lesions resulting from the chronic use of non-steroidal anti-inflammatory drugs (NSAIDs), known as chemical gastritis, remains unclear, and the variable prevalence reported in different studies makes this issue a matter of lively debate. The aim of this study was to evaluate the prevalence and importance of chemical gastritis in patients regularly taking NSAIDs. Owing to the high prevalence of Helicobacter pylori infection, particularly in subjects over 60 years of age, and in view of a possible association with damage, the presence of H pylori infection in the same tissue sample was also determined in all patients. Methods —One hundred and ninety seven subjects were enrolled, 118 of whom were receiving chronic treatment with NSAIDs and 79 of whom were controls, pair matched for age, sex, and clinical symptoms (ulcer-like dyspepsia or upper digestive tract haemorrhage). Antral biopsies taken during upper gastroduodenal endoscopy were assessed for chemical gastritis according to a modified version of Dixon's score, and for helicobacter correlated chronic active gastritis, according to the updated Sydney system. Results —Chemical gastritis was identified in 11 patients taking NSAIDs (9%) and in four controls (5%) (p < 0.05). Helicobacter pylori was detected in 53 patients taking NSAIDs (45%) and in 34 controls (43%). Patients taking NSAIDs had a significantly higher number of erosions and ulcers and worse endoscores than controls. The presence of H pylori did not appear to increase histological damage, ulcer prevalence, or haemorrhagic events. Conclusions —Chemical gastritis is present in a limited number of patients regularly taking NSAIDs, and is not strongly correlated with NSAID induced damage. In many cases of peptic ulcer or upper gastrointestinal bleeding in patients taking NSAIDs, the presence of chemical gastritis or H pylori infection cannot solely account for the development of mucosal damage.